Relationship for some flexibility, mobility and some joints of the body relative lengths accurately scoring football - Ghafori, Harith (Journal of Physical Education, 2010)
The research aims to identify some relationship to a prism and the relative flexibility and mobility of some joints accurately scoring football. The sample was selected from among the participating teams first division football season 2008/2009, for several reasons including the weakness of the scoring in the clear on goal and missed many scoring opportunities near the goal, despite the arrival of the target more than the corresponding group and the participation of all players in every game. The research aims to find a relationship between some of the flexibility of body joints accurately scoring football, and some of the prism and the relative precision scoring football on the other. It has been assumed by the presence of a statistically significant relationship between some of the flexibility of body joints and some of the relative precision prism scoring football. and one of the most important conclusions and recommendations that the researcher is left 1) the accuracy of a target associated with the moral flexibility of joints, some of the body. 2) concern for the development of flexible joints of the body it is a positive impact on the sports movements